ANALYTICAL STUDY ON THE EFFECT OF CONFINEMENT OF R.C. CIRCULAR COLUMN TO THE VALUE OF CURVATURE DUCTLING - Kurdian Suprapto; Tavio Tavio; Yanuar Siscaria Rahmawati (Journal of Civil Engineering, 2010)
Construction technology has been rapidly developing nowadays which often requires the use of higher ductility of structural elements. All structural members, especially columns as primary structural components should have higher ductility so that it can delay the collapse of the buildings during earthquake. There is a significant difference in behavior between unconfined and confined concrete columns. Confined concrete columns show higher ductility compared with those unconfined. To accommodate the analysis, a computer program called MoCurv v.1.2 is developed. This program is an improvement of the earlier developed program called MoCurv v.1. This program can be used to analyze circular column sections with NSC and HSC. Five major factors are dominantly control the value of curvature ductility, i.e. transverse reinforcement spacing, number and size of longitudinal bars, strength of concrete, column size, and axial loading. Parametric study has also been done to compare the effectiveness of each parameter. It can be concluded that the most influencing parameter to the value of curvature ductility is the spacing of transverse reinforcement.